Fibrates for the Treatment of Primary Biliary Cholangitis Unresponsive to Ursodeoxycholic Acid: An Exploratory Study - Cançado, Guilherme Grossi Lopes; Couto, Cláudia Alves; Guedes, Laura Vilar; Braga, Michelle Harriz; Terrabuio, Débora Raquel Benedita; Cançado, Eduardo Luiz Rachid; Ferraz, Maria Lucia Gomes; Villela-Nogueira, Cristiane Alves; Nardelli, Mateus Jorge; Faria, Luciana Costa; Oliveira, Elze Maria Gomes de; Rotman, Vivian; et al. (Frontiers in Pharmacology, 2022)
Aim: Up to 40% of patients with primary biliary cholangitis (PBC) will have a suboptimal biochemical response to ursodeoxycholic acid (UDCA), which can be improved by the addition of fibrates. This exploratory study aims to evaluate the long-term real-life biochemical response of different fibrates, including ciprofibrate, in subjects with UDCA-unresponsive PBC. Methods: The Brazilian Cholestasis Study Group multicenter database was reviewed to assess the response rates to UDCA plus fibrates in patients with UDCA-unresponsive PBC 1 and 2 years after treatment initiation by different validated criteria. Results: In total, 27 patients (100% women, mean age 48.9 ± 9.2 years) with PBC were included. Overall response rates to fibrates by each validated criterion varied from 39 to 60% and 39–76% at 12 and 24 months after treatment combination, respectively. Combination therapy resulted in a significant decrease in ALT and ALP only after 2 years, while GGT significantly improved in the first year of treatment. Treatment response rates at 1 and 2 years appear to be comparable between ciprofibrate and bezafibrate using all available criteria. Conclusion: Our findings endorse the efficacy of fibrate add-on treatment in PBC patients with suboptimal response to UDCA. Ciprofibrate appears to be at least as effective as bezafibrate and should be assessed in large clinical trials as a possibly new, cheaper, and promising option for treatment of UDCA-unresponsive PBC patients.